Food insecurity and its associations with cardiometabolic health in Latino individuals of Mexican ancestry - Verde, Ludovica; Kohler, Lindsay N.; Muscogiuri, Giovanna; Parra, Oscar; Klimentidis, Yann C.; Coletta, Dawn K.; Mandarino, Lawrence J. (Frontiers in Nutrition, 2024)
Background: Latino populations, especially those of Mexican ancestry, face higher rates of both cardiometabolic diseases and food insecurity, compounding negative health outcomes. Food insecurity is associated with poor dietary choices, which not only worsen cardiometabolic health but also contribute to various health complications, making it a critical public health issue in these communities. The aim of this study was to investigate the prevalence of food insecurity and its associations with diet, cardiometabolic risk factors, and glycemic control among Latino individuals of Mexican ancestry.Methods: Cross-sectional observational study using data from the El Banco por Salud biobank. The study included 1,827 participants with a mean age of 52.5 ± 14.4 years, recruited from communitybased settings. The majority were women (67.6%), obese (mean BMI 32.4±7.0 kg/m²), and sedentary (43.5%). Food insecurity was assessed using the 6-item U.S. Household Food Security Module, while dietary information was obtained using the Brief Dietary Assessment Tool for Hispanics. Primary outcomes included cardiometabolic risk factors and glycemic control, specifically HbA1c levels.Results: Of 1,827 participants, 69.7% were food secure and 30.3% were food insecure. Food insecure participants had a significantly larger waist circumference (p=0.034), consumed poorer quality diets, and had higher HbA1c levels (p=0.043), with the association remaining significant after adjustments (p=0.007 for age, sex, BMI, and waist circumference; p=0.021 for additional sociodemographic factors).Conclusions: The findings reveal that food insecurity among Latino individuals of Mexican ancestry is associated with unhealthy food choices and higher HbA1c levels, exacerbating the risk of poor cardiometabolic health. This underscores an urgent need for targeted interventions to address food insecurity, ultimately promoting better metabolic health outcomes in vulnerable populations.